Kyphoscoliotic Ehlers–Danlos syndrome associated with superior mesenteric artery aneurysm and abdominal aortic rupture: a case report - Li, Jiru; Liu, Keqiang; Zhu, Xiaodong; Xu, Yaya; Xu, Lili; Chi, Runmin; Zhu, Yueniu (Frontiers in Pediatrics, 2026)
Kyphoscoliotic Ehlers–Danlos syndrome (kEDS) is a rare autosomal connective tissue disorder characterized by progressive kyphoscoliosis, congenital muscular hypotonia, marked joint hypermobility, and severe skin hyperextensibility and fragility. Deficiency of lysyl hydroxylase due to variants of the PLOD1 gene has been identified as a pathogenic cause of the disease. Vascular fragility in kEDS has rarely been reported. Here, we report a 15-year-old Chinese boy with kEDS-PLOD1 who presented with a superior mesenteric aneurysm and severe vascular complications. The patient underwent emergency hybrid surgery combining hemostasis by laparotomy and stent graft placement superior to the bleeding artery by endovascular intervention. The patient's presentation improved postoperatively. Unfortunately, the patient died despite medical intervention. Whole exome sequencing identified compound heterozygous variants in the patient's PLOD1 gene: a reported variant, c.1095C > T, and a novel variant, c.1262delC. The c.1262delC variant is a frameshift variant that results in a premature stop codon and loss of gene function. Overall, this case report further expands the genetic landscape of kEDS and suggests that vascular intervention in these patients requires individualized assessment of vessel function and local perfusion status.